Could Biostimulants with Plant Active Compounds Improve the Tolerance to Oxidative Stress in Prosopis alba (Griseb.)? - Santacruz-García, Ana Carolina; Senilliani, Maria Gracia; Gomez, Adriana Teresita; Ewens, Mauricio; Bravo, Micaela; Abraham, Siria; Nazareno, Mónica Azucena (MDPI, 2022)
Presentado al 2nd International Electronic Conference on Forests—Sustainable Forests: Ecology, Management, Products and Trade. Online | 1–15 September 2021